Modulation of Nerve Cell Differentiation: Role of Polyphenols and of Contactin Family Components - Picocci, Sabrina; Bizzoca, Antonella; Corsi, Patrizia; Magrone, Thea; Jirillo, Emilio; Gennarini, Gianfranco (Frontiers in Cell and Developmental Biology, 2019)
In this study the mechanisms are explored, which modulate expression and function of cell surface adhesive glycoproteins of the Immunoglobulin Supergene Family (IgSF), and in particular of its Contactin subset, during neuronal precursor developmental events. In this context, a specific topic concerns the significance of the expression profile of such molecules and their ability to modulate signaling pathways activated through nutraceuticals, in particular polyphenols, administration. Both in vitro and in vivo approaches are chosen. As for the former, by using as a model the human SH-SY5Y neuroblastoma line, the effects of grape seed polyphenols are evaluated on proliferation and commitment/differentiation events along the neuronal lineage. In SH-SY5Y cell cultures, polyphenols were found to counteract precursor proliferation while promoting their differentiation, as deduced by studying their developmental parameters through the expression of cell cycle and neuronal commitment/differentiation markers as well as by measuring neurite growth. In such cultures, Cyclin E expression and BrdU incorporation were downregulated, indicating reduced precursor proliferation while increased neuronal differentiation was inferred from upregulation of cell cycle exit (p27–Kip) and neuronal commitment (NeuN) markers as well as by measuring neurite length through morphometric analysis. The polyphenol effects on developmental parameters were also explored in vivo, in cerebellar cortex, by using as a model the TAG/F3 transgenic line, which undergoes delayed neural development as a consequence of Contactin1 adhesive glycoprotein upregulation and premature expression under control of the Contactin2 gene (Cntn-2) promoter. In this transgenic line, a Notch pathway activation is known to occur and polyphenol treatment was found to counteract such an effect, demonstrated through downregulation of the Hes-1 transcription factor. Polyphenols also downregulated the expression of adhesive glycoproteins of the Contactin family themselves, demonstrated for both Contactin1 and Contactin2, indicating the involvement of changes in the expression of the underlying genes in the observed phenotype. These data support the hypothesis that the complex control exerted by polyphenols on neural development involves modulation of expression and function of the genes encoding cell adhesion molecules of the Contactin family and of the associated signaling pathways, indicating potential mechanisms whereby such compounds may control neurogenesis.